Jacob‐induced transcriptional inactivation of CREB promotes Aβ‐induced synapse loss in Alzheimer's disease. (3rd January 2023) - Grochowska, Katarzyna M; Gomes, Guilherme M; Raman, Rajeev; Kaushik, Rahul; Sosulina, Liudmila; Kaneko, Hiroshi; Oelschlegel, Anja M; Yuanxiang, PingAn; Reyes‐Resina, Irene; Bayraktar, Gonca; Samer, Sebastian; Spilker, Christina; et al.
Abstract: Synaptic dysfunction caused by soluble β‐amyloid peptide (Aβ) is a hallmark of early‐stage Alzheimer's disease (AD), and is tightly linked to cognitive decline. By yet unknown mechanisms, Aβ suppresses the transcriptional activity of cAMP‐responsive element‐binding protein (CREB), a master regulator of cell survival and plasticity‐related gene expression. Here, we report that Aβ elicits nucleocytoplasmic trafficking of Jacob, a protein that connects a NMDA‐receptor‐derived signalosome to CREB, in AD patient brains and mouse hippocampal neurons. Aβ‐regulated trafficking of Jacob induces transcriptional inactivation of CREB leading to impairment and loss of synapses in mouse models of AD. The small chemical compound Nitarsone selectively hinders the assembly of a Jacob/LIM‐only 4 (LMO4)/ Protein phosphatase 1 (PP1) signalosome and thereby restores CREB transcriptional activity. Nitarsone prevents impairment of synaptic plasticity as well as cognitive decline in mouse models of AD. Collectively, the data suggest targeting Jacob protein‐induced CREB shutoff as a therapeutic avenue against early synaptic dysfunction in AD. Synopsis: The synapto‐nuclear shuttling protein Jacob assembles and docks a signalosome to the transcriptional regulator CREB to promote CREB de‐phosphorylation and neuronal cell death. Here, β‐amyloid peptide (Aβ) is found to cause Alzheimer‐associated synapse loss by regulating nuclear translocation of Jacob, providing a potential target for therapeutic intervention. Aβ promotes nuclear translocation of Jacob in Alzheimer's disease (AD) patient brains and mouse hippocampal neurons. Aβ‐regulated trafficking of Jacob induces transcriptional inactivation of cAMP‐responsive element‐binding protein (CREB), leading to synapse impairment and loss in an AD mouse model. The small‐molecular compound Nitarsone selectively prevents the assembly of the Jacob/LMO4/PP1 signalosome to promote CREB transcriptional activity. Nitarsone prevents synaptic plasticity impairment and cognitive decline in mouse models of AD. Abstract : A process by which β‐amyloid peptide regulates nuclear trafficking of the synapto‐nuclear shuttling protein Jacob to cause synapse impairment and loss in an AD mouse model can be inhibited by the small molecule Nitarsone.